Effects of essential oil of Eucalyptus globulus loaded in nanoemulsions and in nanocapsules on reproduction of cattle tick (Rhipicephalus microplus) Efectos del aceite esencial de Eucalyptus globulus cargado en nanoemulsiones y en nanocápsulas en la reproducción de la garrapata bovina (Rhipicephalus microplus) - Galli G.M.* (2018)
© 2018, UCOPress. Cordoba University Press (UCOPress Editorial Universidad de Crdoba). All rights reserved.Infestation of cattle tick (Rhipicephalus microplus) produces important lost in the livestock farming. The aim of this study was to investigate whether essential oil of Eucalyptus globulus in different nanosystems (nanoemulsions and nanocapsules) is able to potentiate the negative effect on cattle tick reproduction, interfering on its oviposition and eggs hatchability. Engorged females of R. microplus were obtained from cows naturally infested. In experimental conditions, these females were immersed in tests solutions at concentrations of 1, 5 and 10%, containing pure eucalypt essential oil; and solutions of it in nanocapsules and nanoemulsions, at concentrations of 0.5, 1 and 5%. Tests using pure eucalypt essential oil, at 5 and 10% concentrations, showed 85 and 97.8% of efficacy, respectively. However, the oil encapsulated was not able to potentiate the carrapaticide effect, presenting 61.2% and 50% of efficacy (at 5%), using nanoemulsions and nanocapsules. Therefore, our results allowed us to conclude that essential oil of E. globulus, in its pure form, interfered negatively on reproduction of R. microplus; however, the nanostructured forms had low efficacy.